Memprediksi Kekuatan Otot Punggung: Peran Dominan Kekuatan Genggaman Tangan pada Mahasiswa Pendidikan Olahraga - Saputro, Deny Pradana; Sinulingga, Andrew Rinaldi; Lubis, Ade Evriansyah; Syaputra, Aidil; Purwanto, Purwanto (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2026)
This study aimed to examine the relationships among handgrip strength, trunk extension performance, quadriceps muscle strength endurance, and back muscle strength, and to identify the most dominant predictor of back muscle strength among physical education students. A cross-sectional correlational design was employed involving 38 undergraduate physical education students (age 20.42 ± 0.72 years). Back muscle strength was measured using a back dynamometer, handgrip strength using a grip dynamometer, trunk extension performance using an extension dynamometer, and quadriceps strenght endurance using the wall sit test. Pearson correlation and multiple linear regression analyses were conducted. Handgrip strength showed a strong and significant correlation with back muscle strength (r = 0.839, p < 0.001), whereas trunk extension performance and quadriceps strenght endurance were not significantly associated. Multiple regression analysis revealed that handgrip strength was the only significant independent predictor of back muscle strength (β = 0.838, p < 0.001), explaining 70.7% of the variance in back muscle strength. These findings indicate that handgrip strength serves as a dominant and practical predictor of back muscle strength in physical education students, supporting its use as an efficient screening tool in educational and sport settings.